Analyzing Externalities of Urban Elite Gated Communities: A Case Study in Citraland Gama City Medan North Sumatera - Nina Novira; Muhammad Arif; Elfayetti Elfayetti; Tumiar Sidauruk; Novida Yenni (Jurnal Mamangan, 2025)
Studies on externalities and gated communities are common. However, gated community externalities are rare. This study takes the example of Citraland Gama City (CGC) which was developed on an area of 211.57 ha in the middle of the suburban community of Medan City. The main objective of this study is to determine the positive and negative externalities felt by the surrounding community related to the development of CGC. With a qualitative approach, this study uses observation methods, in-depth interviews, and documentation. The key informants to be interviewed are people living around the housing complex area and people who visit. The results of this study indicate that public perception of CGC provides positive externalities for the community, including public facilities that provide facilities for walking, free hangouts, hanging out, exercising, creating content, and as a shortcut. Another positive externality is providing benefits from the public facilities themselves which include Orchard Road and Boulevard, footpaths, fountains, flyovers, and green infrastructure offered in the middle. However, this also provides negative externalities for the community and the environment. The implications of this study indicate that people who usually sell around the CGC area have lost a strategic location for selling because it is prohibited by the management. The novelty of the study states that the construction of CGC causes changes in land cover from teak plantations to built-up land which results in the loss of rainwater capacity. This is thought to be the main cause of flooding in the surrounding area which had never happened before the CGC.